Development of neurocontrollers with evolutionary reinforcement learning - Yang, X.; Aldrich, Chris (Elsevier, 2005)
Non-magnetized suspensions of magnetite particles with concentrations in excess of 30% by mass and particle size less than 75 Am exhibit Bingham plastic behaviour. When exposed to external magnetic fields of strengths in excess of 41104 T, the rheological behaviour of the suspensions departs from the Bingham model and can be described by a Herschel–Bulkley model of the form s =s0+kcn. The value of the index n was found to range from 0.38 to 0.9, depending on the magnetic field strength, solids concentration and particle size and correlations are proposed for the apparent viscosity of magnetized suspensions as a function of magnetic field strength and solids concentration.